The magazines of geography in Colombia: 20 years after the institutionalization of the discipline (2013)
It was done a review of the evolution of the main academic publications in the field of geography in Colombia, taking as an up dated referent of the geography as profession in Colombia; there were built a balance of the limits in order to preserve this kind publishing projects, the perspectives for the future for the same ones and for the subject in the country. Finally, there were the legacy of some institutions and people to consolidate the knowledge of geography through the magazines.